Association of age with differences in immune related adverse events and survival of patients with advanced nonsmall cell lung cancer receiving pembrolizumab or nivolumab. Issue 5 (June 2020) - Ksienski, Doran; Wai, Elaine S.; Croteau, Nicole S.; Freeman, Ashley T.; Chan, Angela; Fiorino, Leathia; Poonja, Zia; Fenton, David; Patterson, Tiffany; Irons, Sarah; Lesperance, Mary
Abstract: Objectives: To explore the association of age with development of immune related adverse events (irAE) and survival in patients with advanced nonsmall cell lung cancer (aNSCLC) receiving programmed cell death 1 antibodies (PD-1 Ab) outside of clinical trials. Methods: A multicenter retrospective study of PD-1 Ab prescription for patients with aNSCLC between 06/2015–11/2018 at BC Cancer. Multivariable (MVA) logistic regression identified baseline variables associated with irAE manifested within 3 months of PD-1 Ab initiation. Overall survival (OS) analyzed in a propensity-score matched cohort and survival outcomes compared between age groups by stratified log-rank. Six-week landmark analysis was performed and OS compared between patients with interrupted versus continuous treatment by log-rank. Results: Of 527 patients, 40.6% were age ≤ 64 years, 40.6% were 65–74 years, and 18.8% were ≥ 75 years. In MVA, ECOG performance status 2/3 ( p  = .034), squamous histology ( p  = .031), and nivolumab therapy (vs. pembrolizumab, p  = .012) were associated with increased odds of irAE by 3 months of treatment. Across age groups no difference existed in any grade irAE ( p  = .98), hospitalization ( p  = 1.0), or corticosteroids use ( p  = .51). The propensity score–matched survival analysis comprised 77 patients from each age group; all covariates were balanced. OS did not differ significantly by age in the matched cohort ( p  = .17). Treatment interruption due to irAE at 6 weeks was more common in patient ≥75 years (vs. <75, p  = .055) and correlated with lower OS ( p  = .002). Conclusion: In this cohort of patients with aNSCLC treated in routine clinical practice with PD-1 Ab, immune-toxicity and observed survival were similar amongst age groups.